E-MAGAZINE SEBAGAI MEDIA ALTERNATIF PENYEBARAN KONSEP DESAIN KOMUNIKASI VISUAL - Petrus Gogor Bangsa (Ars: Jurnal Seni Rupa dan Desain, 2008)
The dissemination o f the visual communication design works greatly depends on the employedmedia. So far, design works can be accessed through books and design magazines and their applied media.Meanwhile, there are many obstacles in accessing books and design magazines because ofbolh its rarity andits relative expensive price. Nowadays, internet technology and the work saving in digital formal solve thisproblem. E-magazine, which was initiated by the youngsters, is the ideal tool to be a media o f expressionand works dissemination. It is answering the challenges o f the creative economy era.Keywords: e-magazine, visual communication design, the media o f expression, creative economy